Assessment of PGC1α-FNDC5 Axis in Granulosa Cells of PCOS Mouse Model - Sh Bakhshalizadeh; F Rabiee; R Shirazi; K Ghaedi; F Amidi; MH Nasr-Esfahani (JRI, 2018)
Background: Polycystic ovarian syndrome (PCOS) is a metabolic and endocrine disorder which is characterized by hyperandrogenism, anovulation or oligomenor-rhea and polycystic ovarian morphology. It is believed that modulation in metabolism of granulosa cells of PCOS patients may lead to infertility. One of the metabolic modulators is FNDC5 and its cleaved form, irisin. The axis of PGC1α- FNDC5 pathway is one of the main factors affecting cellular energy balance the purpose of this study was to evaluate this pathway in granulosa cells derived from PCOS mice model in comparison with control group. Methods: In the present study, PCOS mouse model was developed by injection of dehydroepiandrosterone (DHEA) hormone in 20 mice for a period of 20 days. Also, 20 uninjected mice were used as the control. Meanwhile, a vehicle group consisted of mice which received daily subcutaneous sesame oil injection (n=20). Relative expressions of PGC1α and FNDC5 in granulosa cells were evaluated by RT-qPCR. Analysis of gene expressions was calculated by the ΔΔCT method and the relative levels of mRNA were normalized to GAPDH transcript levels. Differences in genes expression among three groups were assessed using one-way ANOVA, Tukey's Post Hoc test. Results: Our results showed that expression of FNDC5 was significantly reduced in granulosa cells of DHEA-induced PCOS mice compared with control and vehicle groups (p<0.05), while there was no significant differences in PGC1α expression among different groups. Conclusion: Down regulation of FNDC5 transcript level may contribute in metabolic disturbance of granulosa cells derived from PCOS ovary apart from PGC1α levels which remained unchanged.